MENELADAN SIKAP PAUS YOHANES PAULUS II DALAM MENUMBUHKAN BUDAYA PERDAMAIAN DI TENGAH KELUARGA - Albert I Ketut Deni Wijaya (Lembaga Penelitian STKIP Widya Yuwana, 2018)
All mankinds in over the world wants and hopes for peace coming true so much. Peaceful must be begun from family environment, because children learn anything easily and fastly by imitating and watching adult behavior. In this context, it is necessary to learn from Pope John Paul II, who always fight for peace during his life. He believes that peace could be reach from the familiy where it values established and from the comunities where it can be accelerated.